2009
DOI: 10.1002/pssa.200881600
|View full text |Cite
|
Sign up to set email alerts
|

In‐phase and anti‐phase interference fringes in Laue case

Abstract: By using X‐rays from synchrotron radiation, we measured the rocking curves due to only the imaginary part of the atomic scattering factor in Laue case. The interference fringes are observed which are totally different from the Pendellösung fringe. The fringes of the diffracted and transmitted rocking curves are in‐phase with each other. We studied the origin of the in‐phase fringes by using the complex dispersion surface and the electric field in the crystal, and also the relation with a coupled pendulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1 Introduction The Pendello ¨sung fringe has been studied extensively, as it is a peculiar phenomenon to the X-ray dynamical diffraction [1,2]. In our previous work [3], by measuring the rocking curves of the diffracted intensities I h and the transmitted intensities I t of GaAs 200 reflection in Laue case, it is shown that the phase difference Dw between the interference fringes of I h and I t is p when the diffraction occurs only by the real part f 0 þ f 0 of the atomic scattering factor, and zero when the diffraction occurs only by the imaginary part f 00 . Here, f 0 is normal atomic scattering factor and f 0 is real part of the anomalous scattering factor.…”
mentioning
confidence: 99%
“…1 Introduction The Pendello ¨sung fringe has been studied extensively, as it is a peculiar phenomenon to the X-ray dynamical diffraction [1,2]. In our previous work [3], by measuring the rocking curves of the diffracted intensities I h and the transmitted intensities I t of GaAs 200 reflection in Laue case, it is shown that the phase difference Dw between the interference fringes of I h and I t is p when the diffraction occurs only by the real part f 0 þ f 0 of the atomic scattering factor, and zero when the diffraction occurs only by the imaginary part f 00 . Here, f 0 is normal atomic scattering factor and f 0 is real part of the anomalous scattering factor.…”
mentioning
confidence: 99%